(untitled) (Revista Cocar, 2020)
Contributions of a mathematics teacher identified with jurisdiction with humanizing practice Resumo Estuda a identidade de professor de Matemática que leciona no cárcere e as contribuições da pedagogia social para a humanização dos detentos. Emergiu no Programa de Pós-Graduação em Educação em Ciências e Matemáticas do Instituto de Educação Matemática e Científica (IEMCI/UFPA). Objetiva examinar as contribuições do professor de Matemática para a humanização dos sujeitos e suas práticas para facilitar o processo ensino-aprendizagem no cárcere. Fundamenta-se em Ciampa (2001), Dubar (2009), Graciani (2014); Mendes (2014), Pimenta (2005); Valente (2017). Método qualitativo, pesquisa bibliográfica, documental e estudo de campo com entrevista. Como resultados: identidade é processo, o professor de Matemática cria possibilidade para melhorar o processo ensino-aprendizagem, sofre preconceitos, falta de recursos e de condições de trabalho. A violência é fruto da prisionização que modifica identidades, embrutece e pede pedagogia humanizadora e a valorização dos educadores. Palavras-chave: Identidade. Professor de Matemática.. Educação no Cárcere. Abstract It studies the identity of a mathematics teacher who teaches in prison and the contributions of social pedagogy to the humanization of detainees. Emerged in the Graduate Program in Science and Mathematics Education of the Institute of Mathematical and Scientific Education (IEMCI / UFPA). It aims to examine the contributions of mathematics teachers to the humanization of subjects and their practices to facilitate the teaching-learning process in prison. It is based on Ciampa (2001), Dubar (2009), Graciani (2014); Mendes (2014), Pimenta (2005); Valente (2017). Qualitative method, bibliographic research, documentary and field study with interview. As a result: identity is process, the mathematics teacher creates the possibility to improve the teaching-learning process, suffers prejudice, lack of resources and working conditions. Violence is the result of imprisonment that changes identities, generates, demands humanizing pedagogy and the appreciation of the educators. Keywords: Identity. the Mathematics Teacher. Prison Education